Integration of macroscopic fungal diversity in the Banyak mountain forest area into the fungi e-module: Validity and practicality analysis - Nurzahra, Vakha Yulia; Muzazzinah, Muzazzinah; Indrowati, Meti (Univeritas Papua, 2025)
Developing an e-module for biology education is necessary to optimize the learning process. This research aims to evaluate the validity and practice of the macroscopic fungal diversity e-module found in the Banyak mountain forest area, Sragen Regency, as a fungi learning resource. This research employs a research and development (R&D) approach using the ADDIE development model. The e-module was validated by four validators: two media experts and two content experts. At the same time, the practicality test was conducted through individual and small group trials with Xth-grade students. The data collection instruments included a validity assessment sheet for the media and content, as well as a student response questionnaire. Data analysis was conducted both qualitatively and quantitatively, with qualitative data including suggestions and comments from evaluators, while quantitative data were based on evaluator assessments using a Likert scale. The results show that the media validity score was 94%, categorized as very valid, the content validity score was 89%, categorized as very valid, and the practicality test yielded an average score of 87%, categorized as very practical. Based on these results, it can be concluded that the e-module on macroscopic fungal diversity is valid and practical as a learning resource on fungi at a high school in Tangen and can proceed to the next phase, effectiveness testing.